Mio-Pliocene glaciations of Central Patagonia: New evidence and tectonic implications Glaciaciones mio-pliocenas en Patagonia central: nueva evidencia e implicancias tectónicas - Yves Lagabrielle; Bruno Scalabrino; Manuel Suárez; Jean-Francois Ritz (Andean Geology, 2010)
Patagonia is well known for spectacular oceurrences of a variety of glacial-derived landforms and deposits and for a long history of ancient glaciations. In this paper, we first review the diverse evidence that demonstrates the development of glacial-related sedimentary units within the Central Patagonian Cordillera since 7 Ma. Well preserved glacial landforms at the top surface of mesetas on both sides of the Lago General Carrera-Buenos Aires are described: the Meseta Guenguel to the north, and the volcanic Meseta del Lago Buenos Aires to the south. The latter meseta corresponds to a 3 Ma old, morphologically inverted paleo-piedmont, based on Ar/Ar dates of the uppermost lava flows. It shows evidence of glacier advances to the NE direction. Over a distance of 20 km, glacial landforms observed by remote sensing data and digital elevation model define glacial tongues that were fed by the Cordillera reliefs to the west. These lobes are now beheaded from their westward sources along a morpho-structural corridor that bounds the Meseta del Lago Buenos Aires to the west. These remnants can be correlated with the oldest glacial landforms recognized north of Lago General Carrera-Buenos Aires, on the Meseta Guenguel that form the Chipanque moraine system. From these features it is concluded that the glacial drainage network of Central Patagonia has been strongly modified following relief inversion in response to erosion processes and to tectonic causes. Changes occurred after 3 Ma, from a smooth piedmont surface covered by an extensive ice mantle ending with ampie glacial lobes, to the current series of deeply incised glacial valleys such as the Lago General Carrera-Buenos Aires depression. These new data bear important con-straints on the history and development of the first glaciations in southern South America. Patagonia es bien conocida por una espectacular geomorfología glacial y por una larga historia de antiguas glaciaciones. En este artículooprimero se describe la variada evidencia que demuestra el desarrolloo, desde hace 7 Ma, de unidades sedimentarias glacigénicas en la Cordillera Patagónica Central. Luego se describe una bien preservada geomorfología glacial en la cima de mesetas expuestas a ambos lados del lago General Carrera-Buenos Aires: en la Meseta Guenguel en el lado norte y en la meseta volcánica del lago Buenos Aires en el lado sur. Esta última corresponde a un paleo-piedemonte morfológicamente invertido de 3 Ma acorde a edades Ar/Ar de las lavas basálticas superiores. Exhibe evidencia del avance de glaciares hacia el NE. Observaciones hechas con sensores remotos y con modelos de elevación digital evidenciaron la presencia de formas glaciales a loolargo de una distancia de 20 km, las que fueron alimentadas desde los relieves cordilleranos ubicados al oeste. Estos lóbulos están ahora descabezados de su fuente ubicada al oeste a loolargo de un corredor morfoestructural que limita la Meseta del lago Buenos Aires por el oeste. Estos remanentes pueden ser correlacionados con las formas glaciales más antiguas reconocidas al norte del lago General Carrera-Buenos Aires en la Meseta Guenguel y que forman el sistema de morrenas Chipanque. Sobre la base de estos antecedentes se concluye que el sistema de drenaje de la Patagonia Central ha sido fuertemente modificado subsecuentemente a la inversion del relieve en respuesta a procesos erosivos y a causas tectónicas. Hubo cambios después de 3 Ma, desde una suave superficie de piedemonte cubierta por un extenso manto de hielooterminando con amplios lóbulos glaciales, hasta la actual serie de valles glaciales profundamente incididos tales como la depresión del lago General Carrera-Buenos Aires. Estos nuevos datos entregan importantes antecedentes a la historia y desarrolloode las primeras glaciaciones cenozoicas del sur de América del Sur.